Physical chemistry from a different angle : introducing chemical equilibrium, kinetics and electrochemistry by numerous experiments /: introducing chemical equilibrium, kinetics and electrochemistry by numerous experiments. ([2016]) - Job, Georg; Rüffler, Regina
No abstract available